The Creation of Dystopian Fear in Park Eun Kyo’s The Silent Sea (2021) - Karima Ulya; Atinia Hidayah (Metaphor, 2023)
Dystopian is a dark side reflection of human society. This study aims to investigate the dystopian fear in series “The Silent Sea” (2021) written by Park Eun Kyo. The data were collected from the subtitles and focus on the dystopian fears and the effects on characters that appeared in the series. The present study employs M. Keith Booker’s theory (1994) as its analytical tools. The analysis shows that dystopian issues is always highly related to the issues in real world, even though the setting of time and place for dystopian world is far distant from nowdays society, but the real reference of dystopian issues are concreete and nera-at-hand. The analysis also reveals that in the series citizens lived below moderation and they also contributed to the existence of rebellion. However, because of how strong government impact in dystopian world is, all kind of attempts against the government is impossible to be achieved. This study is expected to provide an alternative analysis and reference to literary works belong to dystopian genre.